The effect of soccer players` positional role in Iran Super League on sport injury rates - Zarei, M.; Rahnama, N.; Rajabi, R. (World Journal of Sport Sciences, 2009)
The risk of injury in soccer is considerable. The purpose of this study was to evaluate the effect of soccer players` positional role in Iranian premier league on sport injury rates. Videotapes of 125 out of 240 matches of Iranian soccer premier league during the 2006-07 seasons were selected and analyzed by video analysis system and injury information and positional roles of injured players were recorded. 306 injuries occurred in these 125 matches. Midfielders were the most frequently injured players (P<0.05); than others. Strikers (88.1) and midfielders (72.65) were more prone to injuries in the offensive phase, whereas defenders (86.15) and goalkeepers (91.8) were more susceptible when defending. Most injury mechanisms were classified as being contact (86.1%). The results showed that the most frequent injuries, mechanism of injury and anatomical location of an injury were different in different positions. This information helps players, coaches and physicians to plan preventive and treatment programs.